Conducting a phase III clinical trial in children during the COVID- 19 pandemic: Experience and lessons learnt from a clinical research facility of Nepal - Ram Hari Chapagain; Jessica Maharjan; Santosh Adhikari; Prabhat Thapa; Kshitij Kunwar; Bishnu Rath Giri; Nisha Jyoti Shrestha; Anil Kumar Shrestha; Sanjeet Kumar Shrestha; Suresh Man Tamang; Haeun Cho; Eun Lyeong Park; et al. (Taylor & Francis Group, 2023)
Clinical trials in humans are vital to test safety and efficacy of new interventions and are accompanied with the complexity of related regulatory guidelines, stringent time frame and financial burden particularly when participants are children. Conducting clinical trials in low and middle income countries, where 90% of global diseases occur, increases the complexity as resources, infrastructures, and experience related to clinical trials may be limited in some countries. During the COVID-19 pandemic, due to multiple infection control measures such as social distancing, lock-down of the societies, and increased work load of hospital workers, conducting clinical trials seemed very challenging. Related guidelines and recommendations on clinical trials required updates to adapt the situation for ongoing clinical trials to be continued and new clinical trials to be initiated. In this review report, we described the lessons learnt through our experiences, challenges we faced, and the mitigation measures implemented as a response while conducting a phase III clinical trial on a non-COVID-19 vaccine at a government children's hospital during the COVID-19 pandemic. We hope this report will contribute in lowering the obstacles to allow the successful completion of future studies, in countries where people live with the burden of vaccine-preventable diseases.